Pembelajaran Tari Kreasi “Salune Nue” Melalui Metode Demonstrasi Siswa Kelas IX SMP Negeri 8 Kota Sungai Penuh - Emalia, Citra; Setyaningrum, Naomi Diah Budi; Sepdwiko, Deria (ANTHOR: Education and Learning Journal, 2023)
The problem in this study is the Learning of the Creative Dance "Salune Nue" Through the Demonstration Method for Class IX Students of SMP Negeri 8 Kota Sungai Lilin. This study aims to find out how the creation of the "Salune Nue" dance is taught using the demonstration method. The method used is descriptive qualitative. The sample in this study were students of class IX.A, totaling 34 students. Data collection techniques used in this study were tests and documentation.Research in the teaching and learning process must be carried out systematically and continuously so that it becomes meaningful information in decision-making by conducting an assessment to find out the abilities possessed by students in achieving the competencies that have been determined. Where the test used uses the properties of coconut trees and chrysanthemums, in carrying out the test students are asked toform groups where each group consists of 5 students whose results are then displayed in front of the class accompanied by music and the correct floor pattern. Based on the results of the documentation shown through photos of studentactivities, shows that the learning the "Salune Nue" creative dance was given directions by the teacher on how to practice the "Salune Nue" creative dance.